2016
DOI: 10.1093/femsec/fiw094
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community composition in the water column of the deepest freshwater Lake Baikal as determined by next-generation sequencing

Abstract: The composition of bacterial communities in Lake Baikal in different hydrological periods and at different depths (down to 1515 m) has been analyzed using pyrosequencing of the 16S rRNA gene V3 variable region. Most of the resulting 34 562 reads of the Bacteria domain have clustered into 1693 operational taxonomic units (OTUs) classified with the phyla Proteobacteria, Actinobacteria, Chloroflexi, Bacteroidetes, Firmicutes, Acidobacteria and Cyanobacteria. It has been found that their composition at the family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 67 publications
6
47
0
Order By: Relevance
“…This is the first study that describes the diversity and composition of bacterial communities in Lake Issyk Kul, Kyrgyzstan, using next generation sequencing and a high number of sampling points along the vertical gradient. The main finding is that the depth plays a decisive role in the variations of the community structure, which is consistent with the results of other studies conducted in deep lakes such as Lake Baikal in Russia, Crater Lake in the United States, and Lake Tanganyika in Central Africa (Glöckner et al 2000; Urbach et al 2001; Bel’kova et al 2003; De Wever et al 2005; Kurilkina et al 2016) . However, Lake Issyk Kul showed some differences in terms of the composition of the most abundant groups in the different layers, probably related to particular brackish conditions and high oxygenation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is the first study that describes the diversity and composition of bacterial communities in Lake Issyk Kul, Kyrgyzstan, using next generation sequencing and a high number of sampling points along the vertical gradient. The main finding is that the depth plays a decisive role in the variations of the community structure, which is consistent with the results of other studies conducted in deep lakes such as Lake Baikal in Russia, Crater Lake in the United States, and Lake Tanganyika in Central Africa (Glöckner et al 2000; Urbach et al 2001; Bel’kova et al 2003; De Wever et al 2005; Kurilkina et al 2016) . However, Lake Issyk Kul showed some differences in terms of the composition of the most abundant groups in the different layers, probably related to particular brackish conditions and high oxygenation.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have shown the presence of Chloroflexi and Planctomycetes in deep waters (Urbach et al 2001; De Wever et al 2005; Breuker et al 2013; Campbell and Kirchman 2013; Luo et al 2014; Kurilkina et al 2016; Li et al 2018), however, this is the first study showing the dominance of these two phyla, and more specifically of Anaerolineaceae and Phycisphaeraceae-Gimesiaceae, in the deeper layers of a lake. The microorganisms in the deep waters of Lake Issyk Kul face aphotic conditions, higher salinity than in the surface, lower temperatures, high hydrostatic pressure, and high availability of oxygen.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although these assumptions are speculative, future studies should verify them given their ubiquity and quantitative importance in deep freshwater systems. Indeed, the dominance of CL500-11 has been reported in the two largest deep freshwater systems on Earth, the Laurentian Great Lakes (Rozmarynowycz, 2014;Denef et al, 2016) and Lake Baikal (Kurilkina et al, 2016). of the hypolimnion inhabitants.…”
Section: Ubiquity Quantitative Importance and Potential Eco-physiolmentioning
confidence: 98%
“…Some bacteria are decomposers, breaking down organic matter into nitrate, phosphate, and other essential nutrients [1]. The diversity and abundance of microorganisms in lakes can drastically change the water quality of a freshwater system [2]. Cyanobacteria obtain their energy from photosynthesis and provide an important link in the food chain as they introduce oxygen and energy from the sun's light to freshwater systems [1].…”
Section: Introductionmentioning
confidence: 99%